2023
DOI: 10.4236/wjns.2023.131002
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with Super-Pulsed Laser Shows Efficacy for Stroke and Aphasia: Case Studies

Abstract: Background: Brain disorders have become more and more common today, due to both the aging population and the ever-expanding sports community. However, a new therapeutic technology called photobiomodulation (PBM) is giving hope to thousands of individuals in need. Traumatic brain injury (TBI), dementia, post traumatic stress (PTSD) and attention deficit (ADD) disorders are in many cases quickly and safely improved by PBM. PBM employs red or near-infrared (NIR) light (600 -1100 nm) to stimulate healing, protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…We found that PS also had the therapeutic effects in adult mice. We suggest that PS can be an effective treatment for IVH in adults, as has already been shown for treatment of stroke and traumatic brain injury 83 , 84 . However, given the loss of laser energy when passing through the skull, it can be assumed that that PS during deep sleep, when the brain’s drainage system is activated itself 58 , 85 , 86 , can significantly increase the therapeutic efficacy of PS, as has been demonstrated for the night therapy of Alzheimer’s disease 58 , 87 .…”
Section: Discussionsupporting
confidence: 52%
“…We found that PS also had the therapeutic effects in adult mice. We suggest that PS can be an effective treatment for IVH in adults, as has already been shown for treatment of stroke and traumatic brain injury 83 , 84 . However, given the loss of laser energy when passing through the skull, it can be assumed that that PS during deep sleep, when the brain’s drainage system is activated itself 58 , 85 , 86 , can significantly increase the therapeutic efficacy of PS, as has been demonstrated for the night therapy of Alzheimer’s disease 58 , 87 .…”
Section: Discussionsupporting
confidence: 52%
“…Since the treatment of AD is incurable, therapy aimed at reducing the progression of the disease should be applied throughout the life of patients. In this respect, PBM technologies are the most promising, since they are already widely used in the clinical field for the treatment of various brain diseases [ 137 , 138 , 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many brain diseases are associated with impaired LDRSB and suppression of removal of toxins from the brain, including PD, intracranial hemorrhages, brain trauma, and glioblastoma [ 41 , 42 , 43 , 44 , 45 , 177 ]. There are experimental and clinical data suggesting the effective therapy of these brain diseases by PBM [ 29 , 31 , 45 , 137 , 138 , 139 , 140 , 178 , 179 ]. Therefore, nighttime therapy of brain diseases using PBM and other approaches during deep sleep might herald a new era in neurorehabilitation medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Naeser et al [95] had earlier reported the significant benefit of transcranial photobiomodulation in stroke. In a recent case study by Stephan et al [96], laser photobiomodulation was proven to show significant improvements in stroke and aphasia.…”
Section: Strokementioning
confidence: 99%